The Old Testament in the First Discourse on Martyrs - Francisco, Héctor Ricardo (2021)
The aim of this paper is to analyze the use of Biblical Testimonia in the FirstDiscourse of the Holy Martyrs of the Land of Orient (BHO 706). It will be argued thatthe main purpose of the author was not only to promote the cult of their relics but alsoto demonstrate that the persecution was part of God?s plan for the Church. As long asChrist, the Apostles and the Prophets were Models for those suffering persecution, theBiblical text was the testimony of the truth of Christian Martyrdom. Moreover, bystressing the continuity between the Heroes of both Testaments and the Martyrs, theauthor was engaged in a controversy against Marcionism.